Postzygotic mosaicism of a novel PTPN11 mutation in monozygotic twins discordant for metachondromatosis. Issue 5 (2nd February 2022) - Rydzanicz, Małgorzata; Glinkowski, Wojciech; Walczak, Anna; Koppolu, Agnieszka; Kostrzewa, Grażyna; Gasperowicz, Piotr; Pollak, Agnieszka; Stawiński, Piotr; Płoski, Rafał
Abstract: Genetic mosaicism caused by postzygotic mutations is of a great interest due to its role in human disease. Monozygotic twins arising from a single zygote are considered as genetically identical, and any differences likely to be caused by postzygotic events. Thus, phenotypically discordant monozygotic twins offer a unique opportunity to study genotype–phenotype correlation. Here, we present a three‐generation family starting from a pair of monozygotic twins discordant for metachondromatosis due to postzygotic p.(Gln175His) variant in the PTPN11 gene. Both phenotypically discordant monozygotic twins harbor p.(Gln175His), however significant differences in mosaic ratio is observed not only between twins, but also within different tissue types within one individual. Phenotypic manifestation of p.(Gln175His) in examined family clearly depends on allele variant fraction (VAF). Individuals harboring constitutional mutation (VAF 50%) present typical metachondromatosis. Milder phenotype is observed in twin harboring high‐level mosaicism in the tissue of ectodermal origin (VAF 45%), but not in a blood (VAF 5%). Finally, her twin sister harboring low‐level mosaicism in blood (VAF 2%) and nonblood (VAF 12%) tissues is phenotypically normal. Our results provide insights into biological role of mosaicism in disease and further support the usefulness of nonblood tissues as an optimal source of DNA for the identification of postzygotic mutations in phenotypically discordant monozygotic twins.